Pulchritudo tam antiqua et tam nova - Auwers, Jean-Marie; Vanysacker, Dries (Brepols, 2020)
This volume contains twenty-two articles that colleagues and friends of Mathijs Lamberigts, Dean of the Faculty of Theology at KULeuven and Director of the Revue d’histoire ecclésiastique - Louvain Journal Church History, offer him for his 65th birthday. These articles cover all periods in the history of Christianity, from the apocrypha on Saint Matthew to contemporary Christianity, and focus on themes dear to the dedicatee (Pelagianism, Julian of Eclan, Christianity in Flanders, the Louvain’ tradition, the Second Vatican Council).